Significance of the written sources in study of medieval heritage of Ganja - Hаsanov Elnur Latif oglu (Рукописна та книжкова спадщина України, 2024)

(untitled)
The purpose of the study is to include into scientific circulation the historical and literary manuscripts as the ancient written sources on the cultural heritage of the research of the medieval past of Ganja city. The methods used for this study included historical and comparative research metod, chronological, source method. Scientific novelty. The main features of the socio-cultural development, also literary heritage of the Renaissance period in Ganja, Azerbaijan, were determined based on various manuscripts and archival documents for the first time. Conclusions. This research work studies the basic features of manuscripts, different historical documents on the past of Ganja city as the sources in research of the cultural and sociological development during the Renaissance period. The life and creation of such genius persons as Nizami Ganjavi have been studied based on archival materials, various written sources, historical documents, literary samples for the medieval period on the basis of comparative scientific approach. Manuscripts or reprints of original works of prominent personalities, who lived during this period were included in the scientific circulation as a fundamental source. Also, some controversial points on research of the typical features of development of Ganja city, life and activities of the famous historical persons are clarified based on the investigation of the scientific sources and materials.